Structural equation modelling of service quality and corporate image that affect customer satisfaction in private nursing homes in the Bangkok Metropolitan Region - Satsanguan, Lanchakorn; Fongsuwan, Wanno; Trimetsoontorn, Jirasek (My University, 2015)
The reduction in the total fertility rate and the labour force age along with the rise in older persons' global share, caused increasing demand of older persons using long-term care. Nevertheless, some caregivers for older people in nursing homes had restrictions on their response to older persons' requirements and entrepreneurs could not adequately provide staffs for the demands of the elderly. This led to a decrease in customers' confidence in the service quality of nursing homes as the main problem of this study. This problem influenced both corporate image and customer satisfaction. The study researched and developed structural equation modelling of service quality and corporate image that affected customer satisfaction with private nursing homes in the Bangkok metropolitan region. Samples consisted of private nursing homes' service users who were 60 years old or above and their relatives for three months or more. The 219 samples were compiled from 20 private nursing homes in Bangkok, Nonthaburi and Bratum Thani provinces from April to October 2013. Exploratory factor analysis, confirmatory factor analysis and structural equation modelling were used for data analysis. The findings from data analysis indicated that there were significantly direct effects from service quality on customer satisfaction in private nursing homes. There was also a significant impact from service quality on corporate images of private nursing homes. However, there was no direct relationship found between the corporate images and customer satisfaction.
Keywords: Corporate image; Customer of nursing home; Customer satisfaction; Long-term care; Nursing home; Service quality